Testicular fine needle aspiration cytology from a stallion with testicular degeneration after external genitalia trauma. - Papa, F.; Leme, D. (William E Jones Dvm, 2002)
A seven-year-old Quarter Horse had a serious external genitalia trauma with severe swelling of ventrum, penis, prepuce and scrotum after falling over a fence. Appropriated treatment was rapidly started after clinical examination. During recovery period, the spermatogenesis assess by semen evaluation was not possible due to stallion's inability to ejaculate. Therefore, for testicular evaluation fine needle aspiration cytology (FNAC) was performed. The first FNAC showed a deviation of germ cell line towards immature cells, mainly by primary spermatocytes (59.5%) with very few late spermatids and spermatozoa (2.5% each), and an increased Sertoli cells/germ cells ratio (478/100), which characterized testicular degeneration. One month after the first FNAC, the second exam presented a drastic decrease of Sertoli cells/germ cells ratio (7/100) and marked increase of mature cell number, specially by early and late spermatids (50% and 24.5%, respectively). In this case, the results of both FNAC could demonstrate a partial recovery of spermatogenesis activity. Two months later, the stallion had mated two mares successfully and they became pregnant. In conclusion, the adequate treatment allowed a complete recovery of the stallion's reproductive function, and since semen collection was impossible during treatment, testicular FNAC showed to be an efficient diagnostic method for evaluating acute damage in the spermatogenesis.